STEM APPROACH TO PHYSICS STUDY OF FUTURE ENGINES: STUDY OF THE PHENOMENA OF ELECTROMAGNETIC INDUCTION - Slipukhina, Iryna; Bovtruk, Alla; Mieniailov, Serhiy; Maximov, Serhiy; Kalenchenko, Volodymyr (Proceedings of National Aviation University (archive), 2018)
Formulation of the problem. Actuality of the introduction of the STEM approach during general physics study is determined by the need for the formation of competences for conducting practical-oriented research by students from the first year: scientific and engineering methods of understanding reality help future engineers to form the scientific and technological picture of the world. Analysis of research. The phenomenon of electromagnetic induction is a complex subject in the course of general physics; at the same time; it has wide practical application. A modern physical experiment is a universal means for future specialists to acquire relevant research competencies; a computer-oriented system of physical experiment effectively forms the general scientific and professional skills of future engineers. The purpose of the article was to study the didactic peculiarities of the use of scientific and engineering (STEM) research methods in the study of the phenomena of electromagnetic induction by the future engineers in the course of general physics. Methods. theoretical and empirical methods of scientific research are applied: methods of analysis and modeling; pedagogical experiment; observational and praximetric methods for determining the effectiveness; efficiency and practical suitability of the methodical system. Results and discussion. The study of the phenomenon of electromagnetic induction using the computer-oriented system of physical experiment demonstrates the stages of the scientific method of research; which begins with the formulation of the problem; the construction of theoretical models; continues with the hypothesis; followed by experimental verification; the processing of experimental data and their interpretation; the search for additional information; adjustment experiment; the advancement of new hypotheses and their subsequent verification. The STEM approach for the EMI study has been implemented in accordance with the engineering method of research. It was carried out through the design stages; which include: brainstorming; the introduction of methods for implementing the installation; the selection of materials; the creation of a prototype and its multiple testing. Conclusions. The application of different approaches oriented both to scientific research in the computer-based system of physical experiment and to the engineering method using STEM training shows practical applicability and effectiveness: implementation of this aim required the attraction and development of various levels of competencies starting from algorithmic actions to creative approach in the case of self-creation of an experimental installation. It is revealed that STEM is an engineering method in educational research by its content and purpose. Further development requires appropriate organizational and pedagogical conditions for the implementation of the methodical system for physics study of future engineers using STEM.